ANALISIS YURIDIS PERLINDUNGAN HUKUM TERHADAP SAKSI DAN KORBAN DALAM PERSPEKTIF PERKARA PIDANA - April Yanus Laoly; Parningotan Malau (Yurisprudentia: Jurnal Hukum Ekonomi, 2020)
The purpose of this study is to analyze the perspective of Indonesian criminal law about legal protection of witnesses and victims in the perspective of criminal cases. The research method used is to use normative juridical legal research methods. the use of normative juridical legal research methods is carried out with a statute approach and a case approach to obtain results so that they are expected to obtain the results they want to achieve. The results of this study are that legal protection for witnesses and / or victims of trafficking in persons has not been implemented properly. The rights of victims have not been accommodated in the process of investigation, investigation and justice. The legal protection provided does not view witnesses and / or victims as victims, but rather as witnesses to complete evidence and disclose criminal acts to the extent that they provide information before the trial. In the PSK Law which guarantees and protects the rights of witnesses and / or victims of trafficking in human trafficking to provide freedom and security and comfort to witnesses and / or victims in investigations, investigations, prosecutions and trials. In law enforcement, it turns out that witnesses and / or victims still do not get their rights before the law as witnesses and / or victims